2018
DOI: 10.31018/jans.v10i3.1704
|View full text |Cite
|
Sign up to set email alerts
|

Study on infant feeding practices among mothers in rural areas of Faizabad District (U.P.), India

Abstract: The present study was undertaken to find out socio-demographic profile of respondents and to estimate the current feeding practices including breastfeeding, pre-lacteal feeding and complementary feeding. A cross-sectional study was conducted in four blocks namely Haringtonganj, Amaniganj, Bikapur and Sohawal of Faizabad District in 2015. Total 352 lactating mother having children's aged from 6 months to 2 years were interviewed to collect information on pre designed and pretested proforma. The data was tabulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…From table 2 it could be concluded that among the respondents, majority (50%) of them had first child followed by second child (35%) and third child (15%). A number of researcher show a great influence of birth order contributes child's behaviour, career choice, intelligence of child to certain degree but the child born in order of first, second, last or any other doesn't have great importance Gupta (2019).…”
Section: Birth Order Of the Childmentioning
confidence: 99%
“…From table 2 it could be concluded that among the respondents, majority (50%) of them had first child followed by second child (35%) and third child (15%). A number of researcher show a great influence of birth order contributes child's behaviour, career choice, intelligence of child to certain degree but the child born in order of first, second, last or any other doesn't have great importance Gupta (2019).…”
Section: Birth Order Of the Childmentioning
confidence: 99%